Academic Reasoning and Literacy-Based Tests: Evaluating Their Effectiveness in Predicting Prospective Students' Potential in Indonesia - Kusaeri; Mujib, Abdul; Nursalam (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2025)
The enrollment test for prospective students at Islamic State Universities (Perguruan Tinggi Keagamaan Islam Negeri, or PTKIN) in Indonesia carries significant implications-not only for the students themselves but also within the broader social context. Consequently, there is a pressing need for a valid selection instrument capable of objectively predicting the academic potential of prospective students. This study aims to assess the effectiveness of academic reasoning and literacy-based tests as predictors of academic potential among PTKIN applicants. This research adopts a cross-sectional design to analyze the relationship between UMPTKIN scores and students’ Grade Point Averages (GPAs) during their first two semesters. The dataset comprises 2023 UMPTKIN scores and GPAs of 2,161 students from UIN Syarif Hidayatullah Jakarta and UIN Alauddin Makassar. Data were obtained from the National UMPTKIN Committee and the Information Technology Centers and Databases of the respective PTKINs. Data analysis was conducted using SPSS 24, employing descriptive statistics, Pearson correlation, and multiple linear regression. The results reveal a weak correlation between academic reasoning and literacy scores and students' academic performance, though the degree of influence varies across academic programs. These findings underscore the need to develop more targeted selection approaches aligned with the specific characteristics of each academic program in order to enhance academic outcomes at PTKINs. Accordingly, policymakers involved in student selection processes should prioritize the development and implementation of more valid and program-sensitive selection instruments. Abstrak: Seleksi calon mahasiswa di Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) di Indonesia memiliki dampak yang signifikan, baik pada individu mahasiswa maupun dalam konteks sosial yang lebih luas. Untuk itu, diperlukan instrumen seleksi yang valid dan dapat memprediksi potensi akademik calon mahasiswa secara objektif. Penelitian ini bertujuan untuk menguji efektivitas tes penalaran akademik dan tes literasi sebagai prediktor potensi akademik calon mahasiswa PTKIN. Desain penelitian yang digunakan adalah cross-sectional, yang memungkinkan analisis hubungan antara skor UMPTKIN dan Indeks Prestasi Kumulatif (IPK) mahasiswa pada dua semester pertama. Data penelitian mencakup skor UMPTKIN 2023 dan IPK dari 2.161 mahasiswa yang diterima melalui UMPTKIN 2023 di UIN Syarif Hidayatullah Jakarta dan UIN Alauddin Makassar. Data dikumpulkan dari Panitia Nasional UMPTKIN dan Pusat Teknologi Informasi serta Pangkalan Data masing-masing PTKIN. Analisis data dilakukan menggunakan SPSS 24, dengan tahapan: analisis deskriptif, korelasi Pearson, dan regresi linier berganda. Hasil penelitian menunjukkan bahwa secara statistik hubungan antara penalaran akademik dan literasi dengan pencapaian akademik mahasiswa tergolong lemah, meskipun kontribusi masing-masing faktor bervariasi antar program studi. Temuan penelitian ini menyoroti pentingnya pengembangan pendekatan seleksi yang lebih spesifik dan disesuaikan dengan karakteristik masing-masing program studi untuk meningkatkan pencapaian akademik mahasiswa di PTKIN. Karenanya, bagi pengambil kebijakan seleksi mahasiswa di PTKIN, perlunya menekankan instrumen seleksi yang lebih valid dan terfokus pada karakteristik program studi.